) Fresh yield and phytochemical accumulation on spinach grown in different coir types - Machado, R. M. A. (2022)
The objective of this study was to evaluate if coir can replace peat as growing media in spinach production in phytonutrient content and antioxidant activity terms. The effects of four commercial substrates peat; and three coir types: cocopeat, coir-crush chips, and coir medium, on growth, chlorophyll a and chlorophyll b, total:carotenoids, flavonoids, anthocyanins, proline, glutathione content, and glutathione reductase activity were evaluated in spinach (Spinacia oleracea L. ‘Manatee’). Soil blocked spinach seedlings (five seedlings per block) were transplanted into styrofoam planting boxes (100-cm long × 25-cm wide × 10-cm high) filled with 14 L of substrate. Each planting box was irrigated daily by drip with a complete nutrient solution. Yield (fresh yield) in cocopeat and coir medium were similar to those obtained in peat. Leaf-blade total chlorophyll was higher in peat than in the other substrates. However, leaf-blade total carotenoids and anthocyanins were not affected by substrate type and leaf-blade flavonoids and total glutathione (GSH+GSSG) contents were higher in plants grown in the different types of coir than in peat. Leaf-blade proline levels in plants grown in different types of coir were similar to that recorded in plants grown in peat ranging from 3.5 to 4.5 mg 100 g-1 FW. The findings of this study indicate that coir could be an alternative to peat but depends on the coir type.